INTEGRASI KETERAMPILAN ABAD KE-21 BERBASIS 4C DAN LITERASI DIGITAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK PENGUATAN KARAKTER PESERTA DIDIK - Meleza Andora; Salwa Aurumia Firanti; Kasinyo Harto; Irja Putra Pratama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to examine the integration of 21st-century skills based on the 4Cs (critical thinking, creativity, communication, and collaboration) and digital literacy in Islamic Religious Education (IRE) instruction, as well as its impact on strengthening students’ character. This study employs a qualitative approach using a literature review of various relevant national journals. The results of the study indicate that the integration of 4C skills and digital literacy in PAI instruction enhances students’ critical thinking abilities in filtering religious information, fosters creativity in expressing Islamic values through digital media, and strengthens communication and collaboration skills grounded in Islamic values. Furthermore, digital literacy plays a crucial role in fostering religious moderation, digital ethics, and responsible technology use. This integration has also been shown to significantly contribute to strengthening students’ religious character, tolerance, and noble moral values. Thus, PAI instruction that integrates 21st-century skills and digital literacy serves as an effective strategy for addressing educational challenges in the digital age.